Math Creativity Survey for Class 4 Elementary School - Yasa, Arnelia Dwi; Chrisyarani, Denna Delawanti; Wadu, Ludovikus Boman; Wibawa, Aji Prasetya; Kuswandi, Dedy (Universitas Pendidikan Ganesha, 2021)
The development of creativity among school students has received attention and has become a topic of discussion in education policy. The purpose of this study was to explore and describe the creativity of elementary school students in learning Mathematics. This research uses a descriptive approach in the form of a survey. This study involved 200 students from 11 elementary schools. The research instrument is a questionnaire based on 4 aspects, namely, flexibility, originality and elaboration. Descriptive approach was used to analyze the research data. The findings show that students' creativity differs in four aspects. The Fluency Aspect got a score of 3.07 in the medium category. The flexibility aspect got a score of 3,098 in the medium category. The originality aspect got a score of 2.37 in the medium category. The aspect elaboration got a score of 2.47 in the medium category. Based on the results of the study, it can be found that from the four aspects of student creativity in the medium category. The findings suggest that sub-indicators in every aspect of creativity need to be developed and improved.